Integrated scheduling for mobility-assisted Wireless Sensor Networks. (29th July 2011) - Liu, Kebin; Li, Mo; Wang, Jiliang; Ma, Qiang; Li, Minglu
In randomly deployed sensor networks, usually the node density is not uniform. The network lifetime is thus restricted by the sparsely covered regions. One solution to this problem is to send mobile sensors to low-node-density regions to supplement sensing capability. In this study, we show that with a limited number of mobile sensors, the network lifetime can be largely extended under our integrated scheduling on both mobile and stationary sensors. We also address the challenge of concurrently optimising the motion planning of mobile sensors and the duty cycles of stationary sensors. Simulation results show that our approach achieves high performance.